Asuhan Keperawatan Pada Tn.T Keluarga Tn.T Dengan Gangguan Sistem Muskuloskeletal: Gout Arthritis Di Desa Tonjong Dukuh Karanganyar RT 03 RW 04 Kecamatan Tonjong Kabupaten Brebes - Aliyaturofi’ah; Tati Karyawati (STIKES Columbia Asia Medan, 2026)
Gout arthritis is joint inflammation that occurs suddenly due to the accumulation of excess uric acid levels in the body (hyperuricemia). In Indonesia, based on the 2018 Basic Health Research, the prevalence of gout diagnosed by health workers ranges from 11.9% to 24.7%, with the highest rates in the elderly age group. This scientific paper aims to provide family nursing care for Mr. T and family with musculoskeletal system disorder: gout arthritis in Tonjong Village, Karanganyar Hamlet, RT 03 RW 04, Tonjong District, Brebes Regency. The method used is narrative descriptive, focusing on nursing care given to patients according to the stages of the nursing process. The method of data collection includes observation, interview, and documentation. The nursing diagnoses that emerged were impaired physical mobility and knowledge deficit. Nursing interventions included ambulation support, oral medication administration, massage therapy, and health education. After 2 days of nursing implementation, the evaluation results showed that both nursing diagnoses of impaired physical mobility and knowledge deficit were resolved.